2016
DOI: 10.1159/000442147
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Trial of Temsirolimus and Pemetrexed in Patients with Advanced Non-Small Cell Lung Cancer

Abstract: Background: Pemetrexed is an antifolate chemotherapeutic agent approved for use in non-small cell lung cancer (NSCLC). The mammalian target of rapamycin (mTOR) pathway is implicated in lung cancer development and inhibited by temsirolimus. Methods: We performed a phase I study evaluating the combination of pemetrexed and temsirolimus in advanced non-squamous NSCLC. Results: Eight patients were enrolled in this study. The dose-limiting toxicities included grade 4 thrombocytopenia, grade 3 leukopenia and grade 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
(22 reference statements)
0
16
1
Order By: Relevance
“…To determine if concurrent administration of sirolimus can influence pemetrexed-induced activation of TS at the MTD, western blotting with protein derived from PBMC was performed in a total of 18 patients who were treated at the MTD. In contrast to our in vitro and in vivo mouse study, where sirolimus blocked activation of TS in cells/tumor tissue (14), TS activation was only temporarily affected by concurrent treatment of sirolimus ( Figure 2).…”
Section: Pharmacodynamicscontrasting
confidence: 98%
See 4 more Smart Citations
“…To determine if concurrent administration of sirolimus can influence pemetrexed-induced activation of TS at the MTD, western blotting with protein derived from PBMC was performed in a total of 18 patients who were treated at the MTD. In contrast to our in vitro and in vivo mouse study, where sirolimus blocked activation of TS in cells/tumor tissue (14), TS activation was only temporarily affected by concurrent treatment of sirolimus ( Figure 2).…”
Section: Pharmacodynamicscontrasting
confidence: 98%
“…Although these observations still need to be validated, inhibition of TS activation is a mechanism that may support the observation of activity with the combination in this phase I/II study. The combination of pemetrexed and sirolimus in this study was relatively well tolerated, and appeared to have no new safety concern when compared with other combinations of pemetrexed with an mTOR inhibitor except as described below (13,14). Although grade 3 and higher neutropenia frequently occurred in other studies using pemetrexed and mTOR inhibitors (37-60%) (13,14), it was observed in 14% of participants in this study.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations